P Perbandingan Efektivitas Bootstrap dan Tailwind CSS dalam Pengembangan UI Web Responsif - Miftah Faroq Santoso (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study presents a critical evaluation of Bootstrap and Tailwind CSS as front-end frameworks for developing modern, adaptive, and structured web interfaces. The research background highlights that previous studies have primarily focused on Bootstrap, whereas Tailwind CSS has received relatively limited academic attention. A descriptive comparative approach was employed by developing a simple web prototype using both frameworks. The analysis focused on several aspects, including lines of code, maintainability, design flexibility, responsiveness, and development time. The findings indicate that Bootstrap excels in rapid implementation and consistent design, making it suitable for beginners and projects requiring uniformity. In contrast, Tailwind CSS demonstrates efficiency in code utilization and provides higher design flexibility, though it requires more time and expertise in the initial phase. In conclusion, framework selection should be context-driven: Bootstrap is more suitable for projects demanding speed and consistency, while Tailwind CSS is preferable for projects requiring unique and adaptive design.